The Leader Programme as a Model of Institutional Transfer: Learning from Its Local Implementation in France and Lithuania - Chevalier Pascal; Mačiulyté Jurgita; Razafimahefa Lala; Dedeire Marc (European Countryside, 2017)
Between 2007 and 2013, the European Rural Development Policy targets were supported by the LEADER policy, an instrument that can be interpreted differently according to each country. Based on the examples of France and Lithuania, we studied the way in which the institutional organization of the device at local level helps to understand the stakeholders system and how adaptable it is to situations in each of the corresponding countries and project areas. A comparative approach, based on a joint methodology of investigation and analysis, was used on four project areas: Joniškis and Ignalina in Lithuania, and Gévaudan-Lozère and Pays Coeur d’Hérault in France. It shows that, in all cases, a form of “municipalization” of the LEADER programme, or at least a strong integration of the association sector, is dominant and seems to be established. Studying the network of stakeholders helps to identify the interknowledge as well as the interdependency relationships that lie at the heart of the system. The development of the “social capital of individuals” is often an entry point, if not a cornerstone, of the stakeholders system in place. Finally, it is through the analysis of the project selection process that we can truly grasp the characteristics of the new public action mode, in particular by studying the allocation of projects in these local areas.